FORMALIZATION ORGANIZATIONAL-TECHNOLOGICAL SYSTEM CONTROL LIFE CYCLE OF AEROTECHICS - Тамаргазін, О.; Ліннік, І.; Олег, М. (Science-based technologies, 2011)
In the article basic attention is spared design and realization of systems approach in relation to the problem of increase of efficiency and quality of aerotechics due to forming of system morphology of management of it’s life cycle. The offered method is intended for creation informatively compatible technical, structurally organization-al,  functional  and programmatic  methodical  facilities,  which  are  realize  the production  processes  of  design, manufacture  and maintenance,  on  the  unique  methodological  and  logical-information  basis.  This  is  especially important from the point of view to that efficiency of introduction media on all stages of life cycle of aerotechics is provided due to integration of the information-voluntary systems, which provides the system complexing of au-tomation systems of the different functional setting.